Potential Impacts of Improper Irrigation System Design - Haimanote K. Bayabil; Sandra M. Guzman; Fedro S. Zazueta; Dorota Z. Haman (EDIS)
This publication discusses a few major consequences of improper irrigation design. Written by Haimanote K. Bayabil, Sandra M. Guzman, Fedro S. Zazueta, and Dorota Z. Haman, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised August 2022.